Preoperative immune-inflammation index in predicting the diagnosis and adverse pathological features of prostate cancer - Liang, Chao-Long; Li, Wei-Da; Wang, Jian (Frontiers in Oncology, 2025)
BackgroundStudies have reported that the systemic immune-inflammation index (SII) is positively correlated with genitourinary cancers. This study aims to explore the predictive value of preoperative immune-inflammation index for the diagnosis of prostate cancer and its adverse clinical characteristics.MethodsThis study analyzed patients who underwent their first prostate biopsy in the Urology Department of the Affiliated Hospital of Guangdong Medical University from January 2020 to January 2024. The predictive ability of SII for prostate cancer was evaluated, and the correlation between SII and localized prostate cancer and metastatic prostate cancer was explored.ResultsThe SII in the PCa group was significantly higher than in the BPH group (558.14 vs. 515.06, P = 0.022), and SII independently predicted PCa risk (OR = 1.001, P = 0.013). Metastatic PCa patients exhibited higher SII compared to localized cases (694.80 vs. 437.95, P < 0.001), with multivariate analysis confirming SII, neutrophils, lymphocytes, and PSA as independent predictors of metastasis (OR = 1.000, P = 0.044). ROC analysis revealed limited predictive power of SII alone (AUC = 0.559), but its combination with PSA significantly improved accuracy (AUC = 0.791). A comprehensive model integrating SII, age, uric acid, and PSA achieved an AUC of 0.823, outperforming PSA alone (AUC = 0.777).ConclusionsSII enhances the accuracy of PCa diagnosis and metastatic risk prediction when combined with PSA, demonstrating significant clinical utility. Although SII alone has limited predictive value, its cost-effectiveness and accessibility make it a valuable tool for stratified PCa management. Prospective studies are needed to validate its long-term prognostic significance.